The differences of antibiotics effectiveness in therapy of thypoid fever without complications in children at Putra Bahagia Hospital, Cirebon - Muhammad Nurhanif; Insan Sosiawan A Tunru (Yarsi Journal of Pharmacology, 2020)
Background: Typhoid fever remains a health problem, particularly in Indonesia and other developing countries. There are few selection of antibiotics that used for the treatment of typhoid fever.Objective: The purpose of this research was to determine the antibiotic used in the treatment of typhoid fever without complications in children at Putera Bahagia Hospital Cirebon and to see the difference effectiveness.Methods: The research was conducted in retrospective, that is taking medical records of pediatric patients aged 1-15 years with a diagnosis of typhoid fever at Putera Bahagia Hospital, Cirebon, periode of 2011-2014. Statistical analysis was performed using Kruskal-Wallis test, with SPSS 23 program. Results: Found 117 cases that met the inclusion criteria and antibiotics used are chloramphenicol (23.08%), cefixime (11.97%), cefotaxime (11.11%), ceftriaxone (49.57%), and azitromisin (4.27%). The fastest fever’s free-time is ceftriaxone, 42.46 hours (average time) and the shortest treatment duration is azithromycin, which is 4.8 days.Conclusion: In this research, there was no significant difference between fever’s free-time and treatment duration of chloramphenicol, cefixime, cefotaxime, ceftriaxone, and azithromycin.